Comparison Between Two Pharmacologic Strategies to Alleviate Rewarming Shock: Vasodilation vs. Inodilation - Håheim, Brage; Kondratiev, Timofei; Dietrichs, Erik Sveberg; Tveita, Torkjel (Frontiers in Medicine, 2020)
Abstract Rewarming from hypothermia is often challenged by coexisting cardiac dysfunction, depressed organ blood flow (OBF), and increased systemic vascular resistance. Previous research shows cardiovascular inotropic support and vasodilation during rewarming to elevate cardiac output (CO). The present study aims to compare the effects of inodilatation by levosimendan (LS) and vasodilation by nitroprusside (SNP) on OBF and global oxygen transport during rewarming from hypothermia. We used an in vivo experimental rat model of 4 h 15ºC hypothermia and rewarming. A stable-isotope labeled microsphere technique was used to determine OBF. Cardiac and arterial pressures were monitored with fluid-filled pressure catheters, and CO was measured by thermodilution. Two groups were treated with either LS (n=7), or SNP (n=7), during the last hour of hypothermia and throughout rewarming. Two groups served as hypothermic (n=7), and normothermic (n=6), controls. All hypothermia groups had significantly reduced CO, oxygen delivery, and OBF after rewarming compared to their baseline values. After rewarming, LS had elevated CO significantly more than SNP (66.57 ± 5.6/+30% vs. 54.48 ± 5.2/+14%) compared to control group (47.22 ± 3.9), but their ability to cause elevation of brain blood flow (BBF) was the same (0.554 ± 0.180/+81 vs. 0.535 ± 0.208/+75 %) compared to the control group (0.305 ± 0.101). We interpret the vasodilator properties of LS and SNP to be the primary source to increase organ blood flow, superior to the increase of CO.